Association of umbilical cord venoarterial differences, ΔpH, to morbidity and mortality up to twenty years of follow-up - Sundberg, Tiia-Marie ; 0009-0005-0995-5326; Källén, Karin; Zaigham, Mehreen ; 0000-0003-0129-1578 (European Journal of Obstetrics, Gynecology, and Reproductive Biology, 2025)
Introduction/Background: Measurement of umbilical cord blood gases at birth is the gold standard of capturing the metabolic state of the newborn. Dual sampling of umbilical cord vessels is mandatory, yet the longterm predictive value of venoarterial differences, ΔpH, remain undetermined. Previously, large ΔpH showed a protective effect against adverse neonatal outcomes. Objectives: To investigate the association of ΔpH and long-term morbidity and mortality, up to 20 years after birth. Methods: This was a retrospective study of singleton births with cephalic presentation born 1997–2012 at Skåne University hospital in Malmö, Sweden. Umbilical cord blood records were validated and crosslinked to the Swedish Medical Birth Register, Patient Register and the Cause of Death Register. Hazard ratios for diagnosis, according to the International Classification of Disease 10, were estimated for the ≤ 10th/ 10th–90th/≥90th percentiles of ΔpH. Hazard ratios were adjusted for maternal age, smoking, body mass index, parity and gestational age. Results/Discussion: The study population was comprised of 35,171 births, of which 4,956 had small ΔpH (≤0.04), 26,690 normal ΔpH (0.04–0.150) and 3,525 large ΔpH (≥0.150). Cohort characteristics showed that large for gestational age birth weight was associated with large ΔpH (3.6%/4.1%/6.7%), and small for gestational age was associated with small ΔpH (4.9%/2.9%/1.3%). Emergency cesarean section was associated with small ΔpH (21.5%/7.4%/2.0%), vacuum extraction/forceps was associated with large ΔpH (6.0%/6.8%/11.5%). Hazard ratios showed no significant association with either small or large ΔpH for any organ related disease, including mental or behavioral disorders. Conclusion: Using a large cohort of strictly validated umbilical cord blood gases, we found that abnormal ΔpH showed no significant association of increased risk of organ-related morbidity or mortality up to 20- years of age of follow-up.